Penapisan Hematokrit dan Hemoglobin pada Laki-Laki dan Perempuan Usia Produktif di SMA Kalam Kudus II, Jakarta - Wijaya, Christian; Hartono, Vincent Aditya Budi; Suros, Angel Sharon; Gunaidi, Farell Christian; Destra, Edwin (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Hemoglobin and hematocrit are important parameters in assessing anemia and other blood diseases. Hemoglobin transports oxygen from the lungs to the rest of the body, while hematocrit reflects the density of red blood cells in the blood. This community service activity was carried out at Kalam Kudus II High School, Duri Kosambi Village, Jakarta, involving 68 men and women of productive age. Screening activities are carried out by measuring hemoglobin and hematocrit levels using the For-A brand Point Of Care Testing (POCT) tool. The majority of respondents had normal hemoglobin levels (68.9%), while a small percentage experienced mild anemia (21.6%) and moderate anemia (9.5%). The average hemoglobin level was 13.28 g/dL and hematocrit 38.66%. The 18-35 year age group has the highest hemoglobin and hematocrit levels, while the 51-64 year age group has the lowest. Lifestyle factors, nutrition, genetics, and chronic medical conditions influence hemoglobin and hematocrit levels. Regular monitoring is important in detecting and managing anemia and improving public health.